Guatemala: Human Rights and the Myrna Mack Case - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2003)
Two members of the Committee on Human Rights (CHR), NAS member Mary Jane West-Eberhard and NAS/NAE member Morton Panish, undertook a mission to Guatemala to observe the trial of two high-level Guatemalan military officials who were charged with ordering the murder of Guatemalan anthropologist Myrna Mack. She was stabbed to death in 1990, two days after a report for which she was principal researcher, "Assistance and Control: Policies Toward Internally Displaced Populations in Guatemala," was published by the Georgetown University Press. Ms. Mack had been doing research on and writing about the unjust treatment of the internally displaced people in Guatemala. Thirteen years after Ms. Mack's murder—after the case had gone through dozens of courts and countless delays—a general and colonel in the Guatemalan military intelligence apparatus were brought to trial, and one was convicted. This marked the first time in Guatemalan history that a high-level military official had been brought to justice for atrocities he committed during Guatemala's 30-year civil war. This report summarizes the one-month trial proceedings.
Keywords: Behavioral and Social Sciences

Report of the Treasurer to the Council for the Year Ended December 31, 2002 - National Academy of Sciences (The National Academies Press, 2003)

Biographical Memoirs: Volume 83 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 83 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Biographical Memoirs: Volume 82 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 82 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography